USING THYPRO 39 SCALE FOR PREDICTING THE QUALITY OF LIFE IN HYPOTHYROID PATIENTS AT LADY READING HOSPITAL. - Ur Rehman, Mujeeb; Ali, Sobia Sabir; Khan, Nawaz; Ahmad, Ibrar; Ullah, Irfan (Journal of Ayub Medical College Abbottabad, 2020)
ABSTRACT: Background: Thyroid disorders are the second most common endocrine diseases. With regards to Hypothyroidism, it has a slow indolent course over the years, before its diagnosis. Most of the patient, on adequate treatment with biochemical euthyroid status, have generalised symptoms that affect their quality of life. Several tools to assess quality of life in thyroid disorders have been validated and recommended for use for those patients in clinical follow ups. ThyPRO 39 is one of a recently developed thyroid-specific quality of life (QoL) questionnaire applicable to patients with benign thyroid disorders (BTD). Purpose: The purpose of this study was to predict the thyroid-related quality of life (QoL) instrument ThyPRO 39 in patients with Hypothyroidism, who were rendered euthyroid with thyroid replacement therapy prior to the administration of study tool and to assess the internal reliability of this scale in our population. Methods: A sample of 52 patients undergoing maintenance treatment for Hypothyroidism who visited the outpatient Endocrinology clinics at Lady Reading Hospital was included. They were interviewed for their baseline demographic details and details on ThyPRO 39 questionnaire were recorded after a written informed consent. The data was entered and analysed on SPSS 25. The Internal reliability of the ThyPRO 39 scale was assessed for multi-item scales using Cronbach’s alpha coefficient. Results: The ThyPRO 39 scale demonstrated good responsiveness across the whole range of QoL aspects in patients with hypothyroidism. Internal reliability for ThyPRO 39 scale was satisfactory. Cronbach’s Alpha in our study was 0.928, which was comparable to the results of other studies. Conclusions: We suggest implementing this measurement tool as a patient-reported outcome in clinical studies in our indigenous population and further more to utilise it as a screening tool for QoL in clinical management of Hypothyroidism in our routine medical consultations. Key words: thyroid disease, hypothyroidism, quality of life, ThyPRO 39 questionnaire.